Optimalisasi Perkembangan Motorik Halus Anak Usia Dini melalui Kegiatan Membatik Asam Basa: Pendekatan Penelitian Tindakan Kelas - Sochasa, Jamila Ristin; Setiawan, M. Hery Yuli; Widjanarko, Paulus (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to improve children’s fine motor skills through the implementation of acid-base batik activities, to describe the implementation process, and to identify supporting and inhibiting factors in the activity. This research employed Classroom Action Research (CAR) using a cyclical model consisting of planning, action, observation, and reflection stages. The subjects of this study were 13 children in group B aged 4–6 years at TK Pertiwi Papahan 01 in the 2025/2026 academic year. Data collection techniques included observation, documentation, and field notes. The data were analyzed descriptively using a qualitative approach by comparing the results obtained in each cycle. The results showed that the implementation of acid-base batik activities significantly improved children’s fine motor development. Improvements were observed in children’s ability to coordinate hand and eye movements, control finger movements, and enhance accuracy and neatness in completing tasks. In addition, this activity also positively influenced children’s concentration, activeness, and self-confidence during the learning process. Learning activities involving direct exploration and the use of engaging media were proven to create a more enjoyable, active, and meaningful learning environment. Therefore, acid-base batik activities can be used as an effective, innovative, and developmentally appropriate learning strategy to improve fine motor skills in early childhood.